Report on the 10th World Congress of Herpetology - Indraneil, Das (Institute of Biodiversity and Environmental Conservation, 2024)
The article reports on the organisation of the 10th World Congress of Herpetology, in Kuching, Sarawak, 5-9 August 2024.